Criteria children use to choose books in Selected children’s public libraries in Kuala Lumpur and Petaling Jaya / Syahranah Ahmad Raqi - Syahranah , Ahmad Raqi (2007)
This study aims to determine the frequency and main reasons children visit the public libraries, their companions during the visits, criteria for using the library, their book selection strategies and books preferred, to investigate whether children’s demographic profiles are related to frequency, reasons for visits, criteria for using the library, selection strategies and the type of books preferred; to observe their information seeking pattern which explains the choice of books in the libraries, the primary reference sources and services preferred by the children and the problems they faced when using the libraries. A total of 43 children from the ages of seven to twelve years old, are selected as respondents, with 25 of them from Kuala Lumpur Children’s Library and 18 of them from the Bayan Budiman Children’s Library, Petaling Jaya. Two instruments are used to obtain data, which are unobtrusive observations and structured interviews. The former method involved observing the children’s movement from the time they enter the library to the time they select a book to read or borrow. The movements are mapped and translated into a flow chart diagram based on the model proposed by Hayden (2001). What are observed were the children’s skills in locating, accessing and using sources found in the library. The behaviours observed are classified into four dimensions adapted from Belkin, et al’s (1993) Information Search Strategies which include method of interaction, goal of interaction, mode of retrieval and resource considered. After the observation, the children were approached and interviewed using a structured interview instrument. The results indicate the following; (a) a large number of respondents were frequent visitors, regardless of their age, gender or race; (b) they visited the library to read and do their revisions; (c) Chinese parents were more involved in their children’s choice of books then those from the other racial groups; (d) those who are frequent visitors also have positive feeling towards the library; (e) older children prefer libraries based on the size of their collections rather than the attractive environment, strategic location and activities offered; (f) shelf browsing was the most popular method of choosing a book combined with various strategies such as looking for a book by an author or series; finding a book on a subject, visually or physically scanning and recognizing the physical composition of the book; (g) children select fiction over non-fiction for recreational reading, select books based on the cover, storyline, illustrations, colourful design, typography and prefer books written in English; (h) the searching behaviour respondents exhibited is non-linear in nature; (i) respondents are more likely to refer to their companion such as parents or siblings if they face problems when choosing a book; and (j) the type of problems they face include understanding the standard subject headings and mapping these to their needs, verbalizing their need because of their limited vocabulary skills and they would go to the librarians to locate revision books which they need. In conclusion, children tend to exhibit the same searching behaviour as adult, but they use more visual rather than textual information. Therefore, it is important for the libraries to provide adequate and visually stimulating services and sources to facilitate the children’s book searching process.